1989
DOI: 10.1093/carcin/10.5.933
|View full text |Cite
|
Sign up to set email alerts
|

Studies on hypomethylation of liver DNA during early stages of chemical carcinogenesis in rat liver

Abstract: Our finding that the inhibitors of DNA methylation, 5-azacytidine, 5-azadeoxycytidine or adenosine dialdehyde, given after a carcinogen all potentiated initiation suggested that hypomethylation of DNA during repair synthesis of DNA might play a role in the initiation of the carcinogenic process. To examine this aspect further, we have asked the question, do the nodules which develop from initiated cells after promotion with 1% orotic acid exhibit an altered methylation pattern in their DNA? The methylation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…SAM, as a methyl group donor, is an essential cofactor for a variety of MeTases, including DNA MeTases, a group of enzymes responsible for DNA methylation. DNA methylation status contributes to the control of the expression of a variety of genes, including several oncogenes (5)(6)(7)(8). DNA hypomethylation is thought to constitute an early event in some cancers (7) and has been associated with many types of tumor (5,6,9,10).…”
mentioning
confidence: 99%
“…SAM, as a methyl group donor, is an essential cofactor for a variety of MeTases, including DNA MeTases, a group of enzymes responsible for DNA methylation. DNA methylation status contributes to the control of the expression of a variety of genes, including several oncogenes (5)(6)(7)(8). DNA hypomethylation is thought to constitute an early event in some cancers (7) and has been associated with many types of tumor (5,6,9,10).…”
mentioning
confidence: 99%
“…Several evidences of oncogenes and tumor supressor genes DNA methylation indicated the importance of these epigenetics changes under expression control. DNA hypomethylation was directly related to the overexpression of Raf, c-Myc, c-Fos, c-H-Ras and c-K-ras oncogenes and tumor liver formation (Rao et al, 1989). Hypermethylation of tumor suppressor genes has also been demonstrated.…”
Section: The Role Of Epigenetics In Cancermentioning
confidence: 99%
“…It has been shown that several genotoxic hepatocarcinogens (i.e., 1,2-dimethylhydrazine, N-nitrosodiethyamine, N-nitrosomorpholine) cause alterations in DNA methylation, in addition to exerting genotoxic effects [Rao et al, 1989;Münzel et al, 1991;Park et al, 2001]. Recently, it has been suggested that these epigenetic changes may play a leading causative role in carcinogenic process induced by genotoxic agents [Jaffe, 2003;Bombail et al, 2004;Karpinets and Foy, 2005].…”
Section: Epigenetic Alterations During Genotoxic Hepatocarcinogenesismentioning
confidence: 99%